Sex Differences in Risk Preference and c-Fos Expression in Paraventricular Thalamic Nucleus of Rats During Gambling Task - Ishii, Hironori; Onodera, Mariko; Ohara, Shinya; Tsutsui, Ken-Ichiro; Iijima, Toshio (Frontiers in Behavioral Neuroscience, 2018)
Different biological requirements between males and females may cause sex differences in decision preference when choosing between taking a risk to get a higher gain or taking a lower but sure gain. Several studies have tested this assumption in rats, however the conclusion remains controversial because the previous real-world like gambling tasks contained a learning component to track a global payoff of probabilistic outcome in addition to risk preference. Therefore, we modified a simple gambling task allowing us to exclude such learning effect, and investigated the sex difference in risk preference of rats and its neural basis. The task required water deprived rats to choose between a risky option which provided 4 drops of water or no reward at a 50% random chance vs. a sure option which provided predictable amount x (x = 1, 2, 3, 4). The amount and the risk were explicitly instructed so that different choice conditions could be tested trial by trial without re-learning of reward contingency. Although both sexes correctly chose the sure option with the same level of accuracy when the sure option provided the best offer (x = 4), they exhibited different choice performances when two options had the same expected value (x = 2). Males and females both preferred to take risky choices than sure choices (risk seeking), but males were more risk seeking than females. Outcome-history analysis of their choice pattern revealed that females reduced their risk preference after losing risky choices, whereas males did not. Rather, as losses continued, reaction time for subsequent risky choices got shorter in males. Given that significant sex difference features mainly emerged after negative experiences, male and female rats may evaluate an unsuccessful outcome of their decision in different manners. Furthermore, c-Fos expression in the paraventricular nucleus of the thalamus (PV) was higher in the gambling task than for the control task in males while c-fos levels did not differ in females. The present study provides a clear evidence of sex differences in risk preference in rats and suggests that the PV is a candidate region contributing to sex differences in risky decision making.